Practices, Challenges, and Prospects of Online Learning during Covid-19 Pandemic in Higher Education: Lecturer Perspectives - Roy Martin Simamora; Daniel de Fretes; Ezra Deardo Purba; Daniel Pasaribu (Indonesia Approach Education, 2020)
This study aimed to investigate the lecturer' perspectives during COVID-19 pandemic in higher education. The participants have consisted of 8 from various universities in Indonesia. In this study, researchers chose narrative analysis as a research approach. A narrative analysis was used to explore lecturer perspectives or views on e-learning based on the practices, challenges, and prospects during COVID-19 pandemic. Based on the lecturers' perspective, the researchers concluded that online learning applications are beneficial for some lecturers to deliver lecture material without face to face, although there are some obstacles such as inadequate internet access. Some campuses provide self-developed applications to facilitate teaching lecturers and provide access to students to study lecture material. Some teachers also used online learning service provider applications or third parties such as Youtube, Zoom, Google Meet, Google Classroom and other online applications. Overall lecturers in universities can use existing learning applications. Efforts are needed to develop further, train, and improve infrastructure facilities to support online learning in the future. Online learning has high prospects and potential to be applied due to its extremely related to technological developments and ever-changing times wherever everything is quick and economical.